Functional MRI of Native and Non-native Speech Sound Production in Sequential German-English Bilinguals - Treutler, Miriam; Sörös, Peter (Frontiers in Human Neuroscience, 2021)
Bilingualism and multilingualism are highly prevalent. Non-invasive brain imaging has been used to study the neural correlates of native and non-native speech and language production, mainly on the lexical and syntactic level. Here, we acquired continuous fast event-related FMRI during visually cued overt production of exclusively German and English vowels and syllables. We analyzed data from 13 university students, native speakers of German and sequential English bilinguals. The production of non-native English sounds was associated with increased activity of the left primary sensorimotor cortex, bilateral cerebellar hemispheres (lobule VI), left inferior frontal gyrus, and left anterior insula compared to native German sounds. The contrast German > English sounds was not statistically significant. Our results emphasize that the production of non-native speech requires additional neural resources already on a basic phonological level in sequential bilinguals.